Out of sight [videorecording (DVD)] - Holmes, David, 1969- (Universal Home Video, 1998)
A career bank robber busts out of jail with the help of his buddy and kidnaps a U.S. Marshal in the process. When the two cons head for Detroit to pull off their final big heist, the Marshal is put on their case but she finds she is attracted to one of them and has second thoughts about bringing them in.